Accuracy of esophageal scintigraphy for evaluation of esophageal motility disorders - Sangsasri, Vana; Sirisalipoch, Sasitorn; Gonlachanvit, Sutep; Chaiwatanarat, Tawatchai (Chulalongkorn Medical Journal, 2023)
Background : Esophageal scintigraphy is a non-invasive tool for detection of esophageal functional abnormality. But the lack of standardized procedure results in a wide range of reported sensitivity and specificity. Concerning the method of data acquisition, some studies found from their data that several swallowing provide a better result than single swallowing technique. Objective : To compare the accuracy of single swallowing and multiple swallowing methods in detection of esophageal functional abnormality using manometry as gold standard. Methods : and Materials Thirty-six patients who were clinically suspected of esophageal motility abnormality were examined using six consecutive swallows of the radiolabeled liquid and semisolid bolus. Six parameters were calculated for each swallowing technique. The first was used to calculate single swallowing parameters. Averages of six swallowing parameters were used as multipleswallowing parameters. All patients were investigated with manometry for their final diagnosis. Results : Twenty-eight patients had abnormal manometry results. Multiple liquid swallows provided the best diagnostic accuracy; all parameters, except mean time, had area under ROC curves of more than 0.85. The mean transit time of 8.8 sec. and emptying of 82% using multiple liquid swallows resulted in the best sensitivity (96%). The semisolid swallowing gave variable results; 2 parameters were better for multiple-swallowing technique, the other 4 parameters were better for single-swallowing technique. Conclusion : Multiple liquid swallowing technique provides best diagnostic accuracy in detection of esophageal functional abnormality. The results of semisolid swallowing varied, probably because it was difficult to standardize the consistency of semisolid bolus.